Metode Kritik Matan Hadis Dengan Pendekatan Alquran Dalam Kaidah Ilmu Naqd Al-Matan - Muhammad Qomarullah (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The Matan Hadith Criticism Method With the Qur'anic Approach in the Rules of Naqd Al-Matan ScienceThis article discusses how the position of al-Qur’ān in analyzing the prophet's hadith in studying the contents of the hadith of the Prophet Muhammad. The method of criticism of this hadith with the interpretation of the al-Qur'ān is not new, because starting from among the Companions like Āishah have already done it, then it becomes a reference for the next scholars. Hadith, which is seen as a source of reference for understanding the Qur'an, is a normative basis in determining legal arguments or statements, because the Prophet has full authority to explain the Koran, the provider of legal statements, and the Messenger of Allah also need to be obeyed and emulated as an ideal human being in applying the contents of al-Qur'ān. However, the hadiths that come from the Messenger of Allah need to be examined a lot because of the varying quality of hadiths so that it becomes a debate about the authenticity of the Messenger of Allah because the problem of the hadiths being different from the contents of the Qur'an, while the Messenger of Allah is unlikely to differ from the Qur'an. Therefore, the Naqd al-Matan method, 'Ilm Mukhtalaf al-Ḥadīṡ and textual contradiction analysis (‘Ilm ta'āraḍ az-Żāhirī) are the methods for analyzing the contradiction. So, the approach of al-Jamu' wa at-Taufīq (compromise), Nāsikh wa Mansūkh, and at-Tarjīḥ as a tool of analysis to find out the location of the problem from the hadith which contradicts al-Qur'ān and to take a common ground in accordance with the absolute truth of Allah from Rasulullah